PSYCHOLOGICAL ASPECTS AND ROLES OF SPORTS ACTIVITY OF STUDENTS (TAMADDUN NURI JURNALI, 2024)
Sports achievement is influenced by various factors such as; physical, technical, tactical and psychological factors. This study aims to see the relationship between self-efficacy factors, achievement motivation, and its relation to self-confidence and their effect on sports performance.